Inspection and monitoring systems subsea pipelines: A review paper. (March 2020) - Ho, Michael; El-Borgi, Sami; Patil, Devendra; Song, Gangbing
One of the largest movers of the world economy is the oil and gas industry. The industry generates billions of barrels of oil to match more than half the world's energy demands. Production of energy products at such a massive scale is supported by the equally massive oil and gas infrastructure sprawling around the globe. Especially characteristic of the industry are vast networks of pipelines that traverse tens of thousands of miles of land and sea to carry oil and gas from the deepest parts of the earth to faraway destinations. With such lengths come increased chances for damage, which can have disastrous consequences owing to the hazardous substances typically carried by pipelines. Subsea pipelines in particular face increased risk due to the typically harsher environments, the difficulty of accessing deepwater pipelines, and the possibility of sea currents spreading leaked oil across a wide area. The opportunity for research and engineering to overcome the challenge of subsea inspection and monitoring is tremendous and the progress in this area is continuously generating exciting new developments that may have far reaching benefits far outside of subsea pipeline inspection and monitoring. Thus, this review covers the most often used subsea inspection and monitoring technologies as well as their most recent developments and future trends.